Cuba's Foreign Policy During Covid-19 Pandemic - Mutiara Dian Hergiati; Honest Dody Molasy; Supriyadi Supriyadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Each country pursues a different foreign policy to overcome the spread of COVID-19. For example, The United States recruit medical staff from overseas, and exporting medical equipment is prohibited in Germany and China. Due to those policies, developing and poor countries have difficulty accessing medical equipment and medical doctors from other countries. In the middle of that situation, Cuba implemented a controversial foreign policy of sending its medical personnel and pharmaceuticals to other countries for free. Cuba faces a similar issue, a large number of COVID-19 patients in the country as well as economic challenges as a result of the US economic embargo. Using theories of health diplomacy, cultivated spill-over, and the concept of symbolic capital, this study argues that the purpose of Cuba's foreign policy of sending its medical personnel overseas is for recognition. International recognition is significant for Cuba as international recognition would encourage other countries to collaborate in the health sector or other sectors with Cuba. Furthermore, Cuba's foreign policy is projected to inspire compassion for countries throughout the world in international forums, which can assist Cuba in resolving international issues, particularly the US economic embargo.